School inspections: a rhetoric of quality or reality? - Gardezi, Sarah; McNamara, Gerry; Brown, Martin; O’Hara, Joe (Frontiers in Education, 2023)
This study aims to explore the perspectives of school inspectors and leaders on the quality of school inspection in four countries with different inspection systems: Dubai, Ireland, New Zealand, and Pakistan. The study also examines the general perceptions of school leaders and inspectors about the impact of quality assurance agencies on teaching and learning in these countries. Using semi-structured interviews of school leaders (n=28) and inspectors (n=14), the research found that school leaders' experiences and perceptions of school inspection and evaluation were varied in and across all four countries. While some expressed dissatisfaction with the inspectors and the process, others considered school inspection indispensable others regarded it as a beneficial endeavor that instilled a sense of vigilance and attentiveness towards the quality standards and inspection criteria. School leaders' experiences and perceptions were almostly positive in Dubai and mixed in the cases of Ireland, New Zealand and Pakistan. Furthermore, the study found a negative correlation between the perception of school leaders and inspectors regarding the quality of inspection practices and their perception of the impact of inspection. Thus, there is a need for open channels of communication between school leaders and inspectors to ensure that school leaders are fully aware of the steps that inspectors take to assure the quality of their practices, which will help eliminate any potential gaps in understanding between the two parties. it is imperative to establish improved avenues of communication to facilitate heightened awareness among school leaders regarding the efficacy of inspectors' work and the comprehensive measures implemented by inspectorates to ensure the quality of their own practices. This initiative will foster enhanced trust between school leaders and inspectors, consequently amplifying the overall influence of school inspections.